THE EFFECT OF COOPERATIVE INTEGRATED READING COMPOSITION (CIRC) ON STUDENTS’ WRITING CRITICAL ESSAY - Niati, Batdal; Rasyidah, Ummi (Universitas Pendidikan Indonesia, 2022)
Essay is the most essential part in writing critical essay. It is one of the subjects that learned by English students. CIRC is a method to improve students’ writing ability. Cooperative integrated reading composition (CIRC) was implemented on students’ writing skill through quasi experimental research; post-test only group design. Sample of the research was thirty nine students. Writing test was used to collect the data and analyzed by using independent t-test. The finding was students who were taught by cooperative integrated reading composition (CIRC) had better scores of writing critical essay than those who were taught by small group discussion. It meant that CIRC give an effect toward students to improve their writing skill.